An oomycete NLP cytolysin forms transient small pores in lipid membranes - Pirc, Katja; Clifton, Luke A.; Yilmaz, Neval; Saltalamacchia, Andrea; Mally, Mojca; Snoj, Tina; Žnidaršič, Nada; Srnko, Marija; Borišek, Jure; Parkkila, Petteri; Albert, Isabell; Podobnik, Marjetka; et al. (Science Advances, 2022)
Microbial plant pathogens secrete a range of effector proteins that damage host plants and consequently constrain global food production. Necrosis and ethylene-inducing peptide 1–like proteins (NLPs) are produced by numerous phytopathogenic microbes that cause important crop diseases. Many NLPs are cytolytic, causing cell death and tissue necrosis by disrupting the plant plasma membrane. Here, we reveal the unique molecular mechanism underlying the membrane damage induced by the cytotoxic model NLP. This membrane disruption is a multistep process that includes electrostatic-driven, plant-specific lipid recognition, shallow membrane binding, protein aggregation, and transient pore formation. The NLP-induced damage is not caused by membrane reorganization or large-scale defects but by small membrane ruptures. This distinct mechanism of lipid membrane disruption is highly adapted to effectively damage plant cells.
CRIS-Team Scopus Importer:2022-03-25